Future Trends in Advanced Materials and Processes - Vizureanu, Petrica (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The Special Issue "Future Trends in Advanced Materials and Processes" contains original high-quality research papers and comprehensive reviews addressing the relevant state-of-the-art topics in the area of materials focusing on relevant or innovative applications such as radiological hazard evaluations of non-metallic materials, composite materials' characterization, geopolymers, metallic biomaterials, etc.